Physical examination & health assessment / Carolyn Jarvis, Ann Eckhardt - Jarvis, Carolyn (Elsevier, 2024)
A concise, practical handbook for the assessment lab and the clinical setting, Jarvis's Pocket Companion for Physical Examination & Health Assessment, 9th Edition makes it fast and easy to review essential assessment skills and techniques. You'll conduct more effective exams by referring to summaries of examination steps, comparisons of normal versus abnormal findings, lifespan and cultural considerations, integration of QSEN safety competencies, and more than 250 full-color photos and drawings. Written by renowned educator and clinician Dr. Carolyn Jarvis, now joined by co-author Dr. Ann L. Eckhardt, this companion handbook is an ideal clinical tool whether you're a beginner who is learning health assessment skills or a practitioner who needs a portable reference!